Disfunción familiar y su relación con la inteligencia emocional en estudiantes del cuarto ciclo de primaria de la Institución Educativa Remanente de Dios, Iquitos 2023 - Montalvan Saldaña, Dany Edith (2025)
This study analyzes the relationship between family dysfunction and emotional intelligence in fourth grade elementary school students. Using a non-experimental quantitative and descriptive correlational design. Data from 171 students were analyzed. The sample used was 100% of the total population. The survey technique was applied and questionnaires were used as instruments. The research revealed a significant relationship between family dysfunction and emotional intelligence, with a p= 0.003 and an Rho=- 0.486 indicating a moderate and negative correlation between the variables. That is, the lower the dysfunctionality, the higher the emotional intelligence. Accepting the study hypothesis.